Evaluation of Thermal Environments in Central Urban Areas (CUAs): Analysis of Existing Focuses and Directions for Future Investigation - Jin, Qiu; Pan, Wenjian (International Journal of Architectural Engineering Technology, 2024)
Central urban areas (CUAs) are particularly vulnerable to rapid environmental changes and contemporary emerging climatic threats, given their complexity of spatial patterns and intensity of human activities. Typically, CUAs exhibit high-density and heterogeneous morphological characteristics through the combination and interaction of various building blocks constructed across multiple ages, showcasing socio-cultural inheritance and ecological-environmental diversity. The scarcity of open spaces and the dense clustering of buildings in these CUAs impede outdoor thermal comfort and ventilation, reducing residents’ opportunities to conduct outdoor activities during extreme weather conditions. Given these circumstances, it is crucial to conduct systematic evaluations of thermal environmental performance in CUAs. Despite widespread global discussion on this topic, conflicting investigation results persist due to the variations in the observation spatial scales, research techniques, analytical approaches, evaluation indices, and socio-geographical contexts. Focusing on the relationships between urban morphological characteristics and outdoor thermal environmental performance, this paper provides an overview of existing related studies across multiple spatial scales and analyses the advantages and shortcomings of prevalent research techniques. The paper aims to outline a systematic framework for investigating the thermal environments in CUAs facing complex social situations and climatic challenges. The paper suggests that integrating both top-down and bottom-up perspectives is important for evaluating thermal environments in CUAs, while a multi-scale investigation should be conducted to identify the essential issues and the underlying mechanisms across various spatial scales. By adding insights from CUAs, the paper seeks to propose suggestions for future improvements in the domain of urban environmental evaluation.